Evaluating Marine Debris Trends and the Potential of Incineration in the Context of the COVID-19 Pandemic in Southern Bali, Indonesia - I Wayan Koko Suryawan; Ariyanti Sarwono; Iva Yenis Septiariva; Chun-Hung Lee (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
Highlight Research:The potential calorific value of marine debris obtained from calculating the total waste is 12.05 MJ/kg, which still falls within the incinerator application's standard criteria. AbstractMarine debris, a global environmental issue today, is a major threat to Bali's seas which are famous for its natural beauty and aggravated by the spread of COVID-19 pandemic. This study aimed to determine the characteristics of marine debris in Bali Island, especially in the southern region and to analyze the feasibility of incineration as one of the waste treatment processes. This research was conducted by utilizing secondary data and literature reviews from related previous studies. Water content and caloric value were measured directly using the ASTM E 790-15 and ASTM D 5865-11a standards. Marine debris generation from 2013 to 2019 tends to decrease from 1.22 kg/km.day to 0.46 kg/km.day. Organic waste (59.4%) comprised the largest marine debris followed by plastic waste (13.4%) and diapers (11.9%). Thermal technology such as incineration can be introduced to treat marine debris. The standard application of incinerator technology is moisture content and caloric value. The water content of marine debris is reportedly 54.56%, therefore, further preliminary processing is needed, especially for waste with high moisture content, such as diapers and organic waste. The potential calorific value of marine debris during the COVID-19 pandemic obtained from calculating the total waste was 12.05 MJ/kg which still did not meet the incinerator application's standard criteria.